Transcripts Expressed during Germination Sensu Stricto Are Associated with Vigor in Soybean Seeds - Ducatti, Karina Renostro [UNESP]; Batista, Thiago Barbosa [UNESP]; Hirai, Welinton Yoshio; Luccas, Daiani Ajala [UNESP]; Moreno, Leticia de Aguila [UNESP]; Guimarães, Cristiane Carvalho [UNESP]; Bassel, George W.; Silva, Edvaldo Aparecido Amaral da [UNESP] (MDPI, 2022)
The rapid and uniform establishment of crop plants in the field underpins food security through uniform mechanical crop harvesting. In order to achieve this, seeds with greater vigor should be used. Vigor is a component of physiological quality related to seed resilience. Despite this importance, there is little knowledge of the association between events at the molecular level and seed vigor. In this study, we investigated the relationship between gene expression during germination and seed vigor in soybean. The expression level of twenty genes related to growth at the beginning of the germination process was correlated with vigor. In this paper, vigor was evaluated by different tests. Then we reported the identification of the genes Expansin-like A1, Xyloglucan endotransgluco-sylase/hydrolase 22, 65-kDa microtubule-associated protein, Xyloglucan endotransglucosylase/hydrolase 2, N-glycosylase/DNA lyase OGG1 and Cellulose synthase A catalytic subunit 2, which are expressed during germination, that correlated with several vigor tests commonly used in routine analysis of soybean seed quality. The identification of these transcripts provides tools to study vigor in soybean seeds at the molecular level.
Keywords: germinative process; molecular tools; seedling establishment